Fricke-gel dosimetry in epithermal or thermal neutron beams of a research reactor. (November 2015) - Gambarini, G.; Artuso, E.; Giove, D.; Volpe, L.; Agosteo, S.; Barcaglioni, L.; Campi, F.; Garlati, L.; Pola, A.; Durisi, E.; Borroni, M.; Carrara, M.; et al.
Abstract: Fricke–xylenol–orange gel has shown noticeable potentiality for in-phantom dosimetry in epithermal or thermal neutron fields with very high fluence rate, as those characteristic of nuclear research reactors. Fricke gels in form of layers give the possibility of achieving spatial distribution of gamma dose, fast neutron dose and dose due to charged particles generated by thermal neutron reactions. The thermal neutron fluence has been deduced from the dose coming from the charge particles emitted by neutron reactions with the isotope 10 B. Some measurements have been performed for improving the information on the relative sensitivity of Fricke gel dosimeters to the particles produced by 10 B reactions, because at present the precision of dose evaluations is limited by the scanty knowledge about the dependence of the dosimeter sensitivity on the radiation LET. For in-air measurements, the dosimeter material can produce an enhancement of thermal neutron fluence. Measurements and Monte Carlo calculations have been developed to investigate the importance of this effect. Highlights: Fricke-gel dosimeters have high potentiality for dosimetry in high fluences of epithermal/thermal neutrons. Fricke-gel dosimeters give the spatial distribution of the absorbed dose. Dosimeters with shape of layer allow separation of all the dose components. TLD measurements and MCNP simulations were performed for evaluations and verifications.